White Matter Correlates of Theory of Mind in Patients With First-Episode Psychosis - Kim, Nahrie Suk; Lee, Tae Young; Hwang, Wu Jeong; Kwak, Yoo Bin; Kim, Seowoo; Moon, Sun-Young; Lho, Silvia Kyungjin; Oh, Sanghoon; Kwon, Jun Soo (Frontiers in Psychiatry, 2021)
Deficits in theory of mind (ToM) are considered as a distinctive feature of schizophrenia. Functional magnetic resonance imaging (fMRI) studies have suggested that aberrant activity among the regions comprising the mentalizing network is related to observed ToM deficits. However, the white matter structures underlying the ToM functional network in schizophrenia remain unclear. To investigate the relationship between white matter integrity and ToM impairment, 35 patients with first-episode psychosis (FEP) and 29 matched healthy controls (HCs) underwent diffusion tensor imaging (DTI). Using tract-based spatial statistics (TBSS), fractional anisotropy (FA) values of the two regions of interest (ROI) – the cingulum and superior longitudinal fasciculus (SLF) – were acquired, and correlational analysis with ToM task scores was performed. Among the patients with FEP, ToM strange story scores were positively correlated with the FA values of the left cingulum and left SLF. There was no significant correlation between FA and ToM task scores in HCs. These results suggest that the left cingulum and SLF constitute a possible neural basis for ToM deficits in schizophrenia. Our study is the first to demonstrate the white matter connectivity underlying the mentalizing network, as well as its relation to ToM ability in patients with FEP.